Efeito de diversos protocolos de dessensibilização dentinária na obliteração de túbulos dentinários, resistência de união do sistema adesivo e formação de camada hibrida na dentina cervical - Escalante-Otárola, Wilfredo Gustavo [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The aim of this study was to evaluate the effect of desensitizing containing calcium phosphate nanoparticles (Ca3(PO4)2) on the bond strength of the adhesive system etch-and-rinse (Scothbond Multi-Purpose), presence of precipitate and obliteration of dentinal tubules and training hybridizing the cervical dentine layer compared to compounds containing potassium nitrate (KNO3) with sodium fluoride (NaF) and / or strontium chloride (SrCl2). No desensitizing was used in the control group (G5). Groups 1, 2, 3 and 4 were treated with 3%KNO3+0.25%NaF, 5%KNO3+0.2%NaF, Ca3(PO4)2+5%KNO3+0.9%NaF e 10%SrCl2+5%KNO3 respectively. The adhesive system was used after the desensitizing treatment. The bond strength (MPa) was evaluated (n = 40 per group) and analyzed fracture pattern. Scanning electron microscopy was used to evaluate the incidence of precipitates on the dentin (500X) and obliteration count of dentinal tubules (1,000x). The confocal laser microscopy was used to quantify the formation of the hybrid layer in the dentin. Regarding the bond strength (MPa) was observed: G3 = G4 = G2 and G2 = G1 = G5, however G3 = G4> G1 = G5. The cohesive fracture was more frequent in G2 (43.8%), G3 (58.5%) and G4 (51.3%). Regarding the presence of precipitates was observed on the dentin: G3> G4 = G2 = G1, G4> G5 and G2 = G1 = G5. Regarding the obliteration of dentinal tubules was observed: G3> G4 = G2, G1 = G2 = G5 and G4> G1 = G5. Regarding the formation of hybrid layer in dentin: G3 = G4> G1 = G2 = G5. All results were evaluated with α = 5%. Ca3(PO4)2 favored the adhesion of the adhesive system in the cervical dentin and provided greater precipitation waste and obliteration of dentinal tubules and hybrid layer formation in the cervical dentin compared to the compounds of KNO3 + NaF.

O objetivo do presente estudo foi avaliar o efeito do dessensibilizante contendo nanopartículas de fosfato de cálcio (Ca3(PO4)2) sobre a resistência de união do sistema adesivo etch-and-rinse (Scothbond Multi-Purpose), presença de precipitado e obliteração de túbulos dentinários e formação de camada hibrida na dentina cervical, comparados aos compostos contendo nitrato de potássio (KNO3) com fluoreto de sódio (NaF) e/ou cloreto de estrôncio (SrCl2). Nenhum dessensibilizante foi utilizado no grupo controle (G5). Grupos 1, 2, 3 e 4 foram tratados com 3%KNO3+0,25%NaF, 5%KNO3+0,2%NaF, Ca3(PO4)2+5%KNO3+0,9%NaF e 10%SrCl2+5%KNO3, respectivamente. O sistema adesivo foi utilizado após o tratamento dessensibilizante. A resistência de união (MPa) foi avaliada (n = 40, por grupo) e o padrão de fratura analisado. Microscopia eletrônica de varredura foi utilizada para avaliar a incidência de precipitados sobre a dentina (500X) e contagem de obliteração de túbulos dentinários (1.000X). A microscopia a laser confocal foi empregada para quantificar a formação de camada hibrida na dentina. Em relação à resistência de união (em MPa) foi observado: G3=G4=G2 e G2=G1=G5, porém G3=G4>G1=G5. A fratura coesiva foi a mais frequente em G2(43,8%), G3(58,5%) e G4(51,3%). Em relação à presença de precipitados sobre a dentina foi observado: G3>G4=G1=G2, G4>G5 e G1=G2=G5. Em relação à obliteração de túbulos dentinários foi observado: G3>G4=G2, G1=G2=G5 e G4>G1=G5. Em relação à formação de camada híbrida na dentina: G3=G4>G1=G2=G5. Todos os resultados foram avaliados com α=5%. O Ca3(PO4)2 favoreceu a adesão do sistema adesivo na dentina cervical, bem como proporcionou maior precipitação de resíduos e obliteração dos túbulos dentinários e formação de camada híbrida na dentina cervical comparados aos compostos de KNO3+NaF.
Effect of different desensitization protocols in dentinal obliteration of dentinal tubules, bond strength and formation of hybrid layer in the cervical dentin
Keywords: Dentin bonding; Dentin; Sodium fluoride; Scanning electron microscopy; Adesivos dentinarios; Dentina; Fluoreto de sódio; Microscopia eletrônica de varredura